Harnessing Citizen Science to Support Nature-Based Flood Management: A Case Study of Photo Post Engagement in the Limb Brook Catchment, Sheffield, UK - Melissa M. Lacey; Cedric Andreasen; Jackie Lowe; John McGlinchey; Patrick Sheard; Claire Bithell; Samuel Lilleker; Martin Reed; Roger Nowell; Rachel Schwartz-Narbonne; Rebecca Sharpe (Environmental Management, 2026)
Nature-based solutions (NBS) are increasingly promoted in climate adaptation strategies to mitigate flood risks and enhance ecosystem resilience. However, the monitoring and evaluation of such interventions remain a challenge due to resource limitations. This paper evaluates a citizen science-based monitoring approach in the Limb Brook catchment (Sheffield, UK), where public photo submissions were used to assess the effectiveness of NBS interventions such as leaky dams and attenuation ponds. Over a 26-month period, over 4500 photographs were collected from 15 fixed photo points. The analysis demonstrates high initial engagement, varied spatial interaction across sites, and the potential for real-time detection of intervention failures. We critically examine how public participation in environmental monitoring can support adaptive flood risk management while highlighting barriers related to data infrastructure, privacy regulations, and long-term community involvement. This study underscores the value of integrating citizen science into national and local policy frameworks for environmental governance.